1997
DOI: 10.1007/s002130050238
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5-HT cell firing in the DRN by non-selective 5-HT reuptake inhibitors: studies on the role of 5-HT 1A autoreceptors and noradrenergic mechanisms

Abstract: Improved clinical antidepressant efficacy may result if the acute inhibition of 5-HT cell firing induced by antidepressants is prevented. Here we examined whether inhibition of 5-HT cell firing by non-selective 5-HT uptake inhibiting antidepressant drugs is reversed by a selective 5-HT1A receptor antagonist. In addition, we examined whether concomitant blockade of NA uptake offsets the inhibition of 5-HT cell firing resulting from 5-HT uptake blockade. Antidepressants which block 5-HT uptake (paroxetine, clomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Although some investigators have reported an attenuation of neuroendocrine or temperature responses mediated by postsynaptic 5-HT 1A receptors following chronic amitriptyline administration (Goodwin et al 1987;Lesch et al 1990), this has not been a consistent observation (Gartside et al 1992;Yamada et al 1994). Neuroendocrine and temperature responses mediated by postsynaptic 5-HT 1A receptors are also attenuated following chronic administration of fluoxetine (Li et al 1996;Lerer et al 1999) or a variety of SSRIs (see Introduction).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some investigators have reported an attenuation of neuroendocrine or temperature responses mediated by postsynaptic 5-HT 1A receptors following chronic amitriptyline administration (Goodwin et al 1987;Lesch et al 1990), this has not been a consistent observation (Gartside et al 1992;Yamada et al 1994). Neuroendocrine and temperature responses mediated by postsynaptic 5-HT 1A receptors are also attenuated following chronic administration of fluoxetine (Li et al 1996;Lerer et al 1999) or a variety of SSRIs (see Introduction).…”
Section: Discussionmentioning
confidence: 96%
“…Although some investigators have reported an attenuation of behavioral and physiological responses mediated by postsynaptic 5-HT 1A receptors (Goodwin et al 1987;Lesch et al 1990), this has not been a consistent observation (Lucki and Frazer 1982;Wozniak et al 1987;Hensler et al 1991;Gartside et al 1992). Electrophysiological studies indicate that chronic treatment with tricyclic antidepressants results in the sensitization of postsynaptic neurons in hippocampus to 5-HT 1A receptor agonists (de Montigny and Aghajanian 1978;Chaput et al 1991).…”
mentioning
confidence: 98%
“…In addition, although St. John's wort has been shown to inhibit the uptake of norepinephrine and dopamine in vitro, it is unlikely that such a blockade would interfere with the ability of serotonin reuptake inhibitors to suppress neuronal activity in vivo. This is supported in part by the fact that dual serotonin/norepinephrine reuptake inhibitors, such as duloxetine and venlafaxine, potently inhibit the firing rate of serotonergic neurons in both the anesthetized and freely moving animal (Gartside et al 1997;Béïque et al 1999;Bjorvatn et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Agents which increase the synaptic availability of serotonin in the brain (e.g., serotonin precursors, releasers, uptake blockers, and MAO inhibitors) produce a compensatory decrease in neuronal activity, by activating somatodendritic 5-HT 1A autoreceptors on serotonergic neurons located within the midbrain raphe (Aghajanian and Wang 1978;Aghajanian and VanderMaelen 1986;Gartside et al 1997). This region may be a selective target for serotonergic antidepressant drugs (Artigas 1993).…”
Section: -Hydroxytryptamine (Serotonin); Electrophysiologymentioning
confidence: 99%
“…Based on their binding affinities, ziprasidone, clozapine, and olanzapine each may act through ␣ 1 receptors (Table 1), antagonists of which are known to inhibit serotonin neuronal firing (Baraban and Aghajanian 1980). Desipramine (DMI) has recently been shown to reverse the inhibitory effect of ␣ 1 antagonists on unit activity (Gartside et al 1997); earlier work had demonstrated similar antagonism with l-amphetamine (Gallager and Aghajanian 1976a) or cirazoline, an ␣ 1 agonist (Lejeune et al 1994). In the present study, DMI (5 mg/kg, I.V.)…”
Section: Sensitivity Of Drug-induced Neuronal Inhibition To Way-1006mentioning
confidence: 99%